KAJIAN LITERATUR KOMPARATIF EFEKTIVITAS INHIBITOR HIJAU BERBASIS EKSTRAK TANAMAN DALAM PENGENDALIAN KOROSI BAJA KARBON - Murtiana Sari, Endah; Rahmat, Rahmat; Nur Laksana, Rifo; Probokusumo, Probokusumo (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Corrosion is a metal degradation process caused by chemical or electrochemical reactions between metals and their surrounding environment. This phenomenon leads to significant technical, economic, and environmental losses in various industrial sectors. The use of synthetic corrosion inhibitors that may cause environmental hazards has encouraged the development of environmentally friendly corrosion inhibitors known as green inhibitors derived from natural materials. This study aims to analyze the effectiveness of plant-based extracts as corrosion inhibitors for steel through a comparative literature review approach. The research was conducted using a systematic literature review by analyzing 30 scientific articles published between 2015 and 2024 obtained from databases such as Scopus, ScienceDirect, and Google Scholar. The analysis focused on several parameters including types of natural materials, active compounds, adsorption mechanisms, inhibition efficiency, and optimum concentration. The results show that mangosteen peel (Garcinia mangostana), papaya peel (Carica papaya), and banana peel (Musa paradisiaca) have significant potential as green corrosion inhibitors with inhibition efficiencies reaching 93–95%, 78–83%, and 65–72% respectively. Active compounds such as tannins, flavonoids, pectin, and alkaloids contribute to the formation of a protective adsorption layer on the steel surface that reduces corrosion rate. These findings indicate that natural materials have strong potential as environmentally friendly and sustainable corrosion inhibitors for future industrial applications.